Odpowiedzi

2010-03-02T17:38:59+01:00
6x-3+4y-8=9
6x+4y=20

10x-15x-5y+3y=2-2
-5x-2y=0
3 2 3
2010-03-02T17:39:32+01:00
3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9/+11
10x-2+3y=15x+5y+2/+2 -15x -5y

6x+4y=20
-5x-2y=4/*2

6x+4y=20
-10x-4y=8

-4x=12/:(-4)
6x+4y=20

x=-3
6*(-3)+4y=20

x=-3
-18+4y=20/+18

x=-3
4y=38/:4

x=-3
y=9,5





2 3 2
Najlepsza Odpowiedź!
2010-03-02T17:47:06+01:00
3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2
6x-3+4y-8=9
10x-2+3y=15x+5y+2
6x-11+4y=9
10x-2+3y=15x+5y+2
6x+4y=20
-5x-2y=4 /*2
6x+4y=20
-10x-4y=8
-------------
-4x=28
x=-7
6x+4y=20
6*(-7)+4y=20
-42+4y=20
4y=62 /4
y=15,5
4 5 4